The Multi-Parameter on-Line Monitoring System Applied for Rotating Machinery - Murčinková, Zuzana; Murčinko, Jaromír; Adamčík, Pavel (Review of Industrial Engineering Letters, 2016)
The paper deals with the designed multi-parameter on-line monitoring system for rotating machinery based on LonWorks Technology. It analyzes the basic theoretical assumptions for its design with the usage of artificial intelligence elements. Moreover, it provides the description of applications of the new monitoring system to production systems of the flexoprinting machines and the small hydroelectric power plant. The effects are in the economy field, i.e. minimization of the production breakdown due to failures, and in the field of environment protection. Thus a modern maintenance characterized by minimizing the costly unscheduled downtime and unexpected breakdowns is presented.